Open arthrolysis for elbow stiffness increases carrying angle but has no impact on functional recovery - Fan, Dapeng (BMC Musculoskelet Disord, 2016)
BACKGROUND: With the exception of normal anatomic changes in the medial collateral ligament and radial head, other factors related to carrying angle changes have not been systematically studied. We reviewed patients who underwent open arthrolysis of the elbow, and evaluated if open arthrolysis could change carrying angle. We then identified factors associated with carrying angle changes. METHODS: Fifty patients with a minimum of 24 months of follow-up after open arthrolysis were evaluated retrospectively. Preoperative and postoperative carrying angles were compared. RESULTS: The carrying angles of 36 elbows in 36 patients were unchanged after surgery (Group A), while the carrying angles of 14 elbows in 14 patients increased postoperatively (Group B). In Group A, mean postoperative extension and flexion were 7° (range 0–24°) and 125° (range 10–135°) respectively, while mean postoperative pronation and supination were 60° (range 50–80°) and 65° (range 30–85°), respectively. In Group B, mean postoperative extension and flexion were 25° (range 0–40°) and 128° (range 60–138°), while mean postoperative pronation and supination were 65° (range 45–85°) and 60° (range 45–75°), respectively. No significant difference in range of motion and Mayo Elbow Performance Score was observed between the two groups. CONCLUSIONS: During open arthrolysis, humeral trochlea debridement and techniques for improving forearm rotation could increase carrying angle. However, this had no impact on elbow functional recovery.